Face & Cie Facéties : Carolus - Duran et compagnie. - Allemand, Evelyne-Dorothée; Ovaere, Emilie; Courbès, Yannick; Musée des Beaux-Arts de Tourcoing, Tourcoing (Paris : ADAGP, 2003)
Bachiri, Brahim ; Bazin, Philippe ; Benzaken, Carole ; Blanc, Jean-Luc ; Bonnat, Léon ; Boutet de Monvel, Bernard ; Cameron, Julia Margaret ; Carrier - Belleuse, Albert-Ernst ; Cazal, Philippe ; Clairin, Georges et al.
Face & Cie Facéties Carolus - Duran et compagnie, Musée des Beaux-Arts de Tourcoing, Tourcoing, du 9 mars au 9 juin 2003
kunstcatalogus
Keywords: Carolus-Duran